Clinical features and prognostic analysis of 120 patients with oropharyngeal squamous cell carcinoma: a hospital-based real-world study - Zhang, Li; Wang, Rui; Wang, Jing; Wang, Dapeng; Ma, Feifei; Li, Zhilin; Wen, Shuxin (Frontiers in Oncology, 2025)
ObjectiveTo investigate the clinical characteristics and current treatment status of oropharyngeal squamous cell carcinoma (OPSCC) patients in Shanxi Province, China, and to examine the relationship between these factors and human papillomavirus (HPV) status, as well as identify risk factors influencing prognosis.MethodsWe retrospectively analyzed the medical records of 120 OPSCC patients from two tertiary hospitals in Shanxi Province. Statistical analyses were performed to assess the relationship between various clinicopathological factors, treatment modalities, and p16 status, as well as their impact on patient prognosis.ResultsThe most common sub-anatomical sites of OPSCC were the tonsils and the base of the tongue, with a significantly higher proportion of p16-positive cases compared to other sub-sites (P = 0.033). The majority of cases were poorly differentiated squamous cell carcinoma (63 cases, 52.5%), of which 71.4% were p16-positive (P = 0.002). Patients with p16-positive OPSCC were more likely to present with a neck mass as the initial symptom (73.2%, P = 0.019). Overall, p16-positive OPSCC patients had a better prognosis (P = 0.008); however, p16-positive patients with primary tumors located in the soft palate and posterior pharyngeal wall did not show a significant prognostic advantage compared to p16-negative patients. Surgical treatment did not improve survival rates for OPSCC patients, particularly in the p16-positive group, where the survival curves showed significant separation approximately one year after treatment, indicating better outcomes in the non-surgical group.ConclusionIn North China’s Shanxi Province, the incidence of HPV-associated OPSCC has surpassed that of OPSCC caused by smoking and alcohol use. p16-positive patients with primary tumors located in the soft palate and posterior pharyngeal wall have a poor prognosis, indicating that treatment de-escalation should be approached with caution. Traditional open surgical treatment, without consideration of HPV status, does not appear to benefit patients.